Pregnancy Induced Hypertension among Pregnant Women Delivering in a Tertiary Care Centre - Fakharunissa, Warda Mehboob, Rubab Naqvi, Shagufta Jabbar, Sabahat Ali Zaidi, Syeda Tahseen Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pregnancy-induced1hypertension (PIH) is the main cause of1maternal & perinatal mortality and can also lead to long-term health problems. It complicates 10% of all pregnancies globally, with pre-eclampsia & eclampsia being the leading causes of maternal & perinatal mortality. Objective: To find the frequency of pregnancy induced hypertension among pregnant women Delivering in a Tertiary Care Hospital. Study Design: Descriptive Cross sectional Methodology: This study was conducted in the Obstetrics and Gynecology Department in Services Hospital, Lahore. Patients present with age 30 to 50 years were included. Preeclampsia was defined as “systolic blood pressure above 140 mmHg and/or diastolic pressure >90mmHg measured at least two times with 4 hours’ interval and proteinuria ≥300mg/day was deemed as preeclampsia and detailed history were given. Total 78 females meeting the selection criteria for the study was included. Prior to birth, pregnant women were interviewed face to face in a different corner of the prenatal ward to collect data on socio-demographic and obstetric factors using a questionnaire. Results: The mean age of the patients with pregnancy induced hypertension was found to be 28.39±4.58. The prevalence of pregnancy induced hypertension was found to be 78 (8.66%) representing 56 (71.79%), 13 (16.6%) and 7 (8.97%) as gestational hypertension, preeclampsia and eclampsia. Conclusion: The prevalence of PIH was high than compared to that of other studies. Gestational Hypertension and Pre-eclampsia was the most common symptoms in PIH.